An Interactive Procedural Environment for Learning Electromagnetic Waves and Radioactivity in Secondary School: The RadiationWorld - Uğur Başlantı; Volkan Bal; Yavuz Akpınar (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
.